Mucosal Shedding and Cellular Immune Response After First Episode Genital Herpes Simplex Virus Type 1 Infection. (4th October 2017) - Johnston, Christine; Son, Hyunju; Magaret, Amalia; Stern, Michael; Gunby, Sarah; Ott, Mariliis; Jing, Lichen; Huang, Meei-Li; Selke, Stacy; Jerome, Keith; Wald, Anna; Koelle, David M
Abstract: Background: Herpes simplex virus type 1 (HSV-1) is the leading cause of first episode genital herpes in the USA. Despite an often severe primary episode, recurrences and viral shedding are less frequent in genital HSV-1 than in genital HSV-2 infection. We sought to understand the relationship between mucosal shedding patterns and the development of the cellular immune response during the first year of genital HSV-1 infection. Methods: Following laboratory documented first episode genital HSV-1 infection, participants obtained daily self-collected genital and oral swabs for two 30-day sessions at 2 months and 11 months post infection. HSV was detected in swabs using real-time quantitative HSV PCR. Blood collected at 12 months was tested for T-cell responses to known CD8+ T-cell HSV-1 peptides by ex vivo IFN-γ ELISpot. Results: Twenty-five persons with documented first episode genital HSV-1 acquisition completed the one year follow-up. Genital HSV-1 shedding was detected in 176 (12.2%) of 1438 swabs from the first shedding session, and declined to 46 (7.1%) of 645 swabs in the second session. There was a trend toward decreased genital shedding in the second compared with the first session among those with primary genital HSV-1 infection (RR = 0.44, 95% CI = 0.12–1.56, P = 0.19). Similarly, genital lesions were detected on 3.8% of days in the first session, and 1.6% of days in the second session. Twenty (80%) of 25 persons had detectable HSV-1-specific T-cell responses, with a median of 2 (range: 1–9) HSV-1epitopes detected per person. Several proteins, including tegument protein VP16 ( UL48 ), ribonucleotide reductase small subunit ( UL40 ), ICP0 ( RL2 ), gB ( UL27 ), and tegument protein VP22 ( UL49 ) stimulated T-cell responses. Conclusion: Genital HSV-1 shedding and lesions appear to decline in the first year after genital HSV-1 acquisition. HSV-1 specific CD8+ T-cells are detectable up to 1 year post infection, despite low recurrence rates. Further characterization of the phenotype of these T-cells will elucidate effective immune responses to genital herpes infection. Disclosures: D. M. Koelle, University of Washingotn: Patent Holder, Patent holder